Analysis of the Innate Immune Response to Febrile UTI in Infants : Evidence of an Acute Cytokine Storm - Ahmadi, Shahram; Rosenblad, Therese; Sabari, Samudra; Linden, Magnus; Brandström, Per; Chao, Sing Ming; Svanborg, Catharina; Ambite, Ines ; 0000-0003-1470-671X (Pediatric Infectious Disease Journal, 2025)
Background: Infections trigger complex immune responses, with conserved as well as disease-specific characteristics. Methods: Proteomic screening technology and gene expression analysis were used here to define the immune response in infants, with their first episode of febrile urinary tract infection. Urine and peripheral blood samples were obtained at enrollment and at follow-up, after 6 months. Results: Pair-wise proteomic analysis of urine samples detected a broad local cytokine response in urine; 20 of the 24 proteins were strongly activated during acute infection compared with follow-up. Functional profiling identified the response as a cytokine storm, and major innate immune response regulators and effector molecules were activated, such as IL-1α, IL-1β, IL-1RA, IL-33, IL-8, IP-10, MCP-1, MIP-1α, MIP-1β, GM-CSF, IL-6, IL-17, TNF-α and IFN-γ. In addition, the adaptive immune response was activated, including CD40L, IL-2, Granzyme B, IL-10, IL-15 and PD-L1. Gene expression analysis of peripheral blood RNA detected a systemic cytokine storm profile, which was more pronounced in infants with renal involvement, defined by positive acute dimercaptosuccinic acid scans, than in infants with febrile urinary tract infection without renal involvement. Conclusions: Local and systemic hyperactivation of innate immunity characterizes acute pyelonephritis, a common and severe bacterial infection in childhood and a significant cause of urosepsis and mortality in adults. The results define a transient cytokine storm response, resembling that induced during severe acute respiratory syndrome coronavirus 2 infection, as characteristic of acute pyelonephritis, rather than individual protein biomarkers.
Keywords: COVID-19; cytokine storm; febrile urinary tract infection; gene expression; immune response; urine proteomics